Problematika Mental Illness dan Solusinya dalam al-Qur’an Perspektif Hamka - Ikrimah Retno Handayani; Hafid Nur Muhammad; Nina Nurrohmah (Universitas Darussalam Gontor, 2024)
The number of suicide cases in Indonesia, a country where Muslims constitute the majority of the population, has unquestionably surprised some Muslims. In Islam, it is prescribed that people should not take another person's life, especially their own. This research uses a literature approach. The purpose of this research is to explore more deeply about mental illness in Hamka's perspective. In essence, every human being can contract mental illness, the only difference is that not all of these problems end in suicide. It can be concluded that according to Hamka, the center of the phenomenon of mental illness is centered on one condition, namely human closeness to God. Humans who have mental health problems (mental illness) are encouraged to get back to know God who created them, follow all things that are commanded, and stay away from things that are prohibited in the Qur'ān